Prevalence, Risk Factors and Mortality Associated with Colonic Atresia: A Population-based Case-control Study - Kankaristo, Roni (My University, 2025)
Purpose This study aims to explore maternal and pregnancy-related risk factors for colonic atresia (CA) and assess the national total prevalence, mortality, and frequency of co-occurring anomalies of this rare malformation in 2004-2017. Methods This case-control study involved 36 cases with congenital CA identified from several Finnish registers. All cases were identified based on the ICD-9/ICD-10 codes and classified based on co-occurring anomalies. Five controls without gastrointestinal congenital malformations matched for residence and time of conception (±1 year) were randomly selected for each case. Maternal risk factors were analyzed with data from the same registers. Results Total prevalence of CA was 0.45/10,000, birth prevalence was 0.37/10,000 and live birth prevalence was 0.36/10,000. The overall prevalence trend did not change (p=0.11) during the study period. There were 15 (41.7%) isolated cases, 3 (8.3%) were associated with known syndromes and 18 (50.0%) had multiple congenital anomalies. Together there were 19.4% (n=7) terminations or neonatal mortalities. An association was observed with maternal diabetes and CA (p=0.03). Conclusion The prevalence of CA in Finland is low with no significant change over the study period. Despite the high frequency of associated anomalies, the overall survival of CA is very high, 97%.
Keywords: colonic atresia, maternal risk factor, congenital anomaly, prevalence